2017
DOI: 10.1101/gad.291336.116
|View full text |Cite
|
Sign up to set email alerts
|

Mcm10 regulates DNA replication elongation by stimulating the CMG replicative helicase

Abstract: Activation of the Mcm2-7 replicative DNA helicase is the committed step in eukaryotic DNA replication initiation. Although Mcm2-7 activation requires binding of the helicase-activating proteins Cdc45 and GINS (forming the CMG complex), an additional protein, Mcm10, drives initial origin DNA unwinding by an unknown mechanism. We show that Mcm10 binds a conserved motif located between the oligonucleotide/oligosaccharide fold (OB-fold) and A subdomain of Mcm2. Although buried in the interface between these domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 51 publications
8
138
1
1
Order By: Relevance
“…In addition, recent studies have indicated that Pol δ sometimes extend the first leading strand primer at an origin before being taken over by Pol ϵ . In vitro assays have identified the minimal protein requirements for both leading and lagging strand synthesis, and for replication fork rates on chromatized DNA consistent with in vivo observations …”
Section: Cmg Helicase Is a Central Scaffold For Replisome Organizationmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, recent studies have indicated that Pol δ sometimes extend the first leading strand primer at an origin before being taken over by Pol ϵ . In vitro assays have identified the minimal protein requirements for both leading and lagging strand synthesis, and for replication fork rates on chromatized DNA consistent with in vivo observations …”
Section: Cmg Helicase Is a Central Scaffold For Replisome Organizationmentioning
confidence: 66%
“…Cell biology studies and in vitro single‐molecule techniques demonstrate that the two CMGs come apart to form two replication forks; each CMG travels 3′‐5′ while encircling ssDNA . The detailed mechanism of these origin initiation steps are still relatively unknown, but successful reconstitution of replication from an origin using recombinant proteins promises detailed mechanistic understanding in the near future . This review focuses on advances in the last 3–4 years on the structure and function of CMG helicase.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Sld2, Sld3, and Dpb11 are released, resulting in formation of the Cdc45/MCM2-7/GINS (CMG) complex Heller et al 2011;Yeeles et al 2015). Interestingly, Mcm10 binding to the CMG is associated with a structural change in the CMG, rendering the complex high-salt-stable (Looke et al 2017) and promoting origin firing (Kanke et al 2012;van Deursen et al 2012;Watase et al 2012;Yeeles et al 2015). The completely assembled CMG complex is highly active in ATP hydrolysis-driven 3 ′ -5 ′ DNA unwinding, as seen first and Cdc6 are released from the OCCM in an ATP hydrolysis-dependent reaction, and, upon recruitment of another Cdc6, the OCM the complex is formed.…”
Section: Initiation Of Dna Replicationmentioning
confidence: 99%
“…However, some plasticity exists, with polymerase δ also playing a role during leading strand DNA synthesis, particularly during initiation of DNA replication and under conditions of replicative stress in budding yeast (Pavlov et al 2001;Devbhandari et al 2017;Yeeles et al 2017) and after homologous recombination-dependent fork restart in Schizosaccharomyces pombe (Miyabe et al 2015). Mcm10 acts also during elongation, as it travels with the replisome (Ricke and Bielinsky 2004;Gambus et al 2006;Pacek et al 2006), and as a specific mutation in its C terminus results in shorter replication products without affecting origin firing (Looke et al 2017).…”
Section: Initiation Of Dna Replicationmentioning
confidence: 99%
See 1 more Smart Citation